A comparison of visual and quantitative assessment of left ventricular ejection fraction by cardiac magnetic resonance. - Holloway, C; Edwards, L; Rider, O; Fast, A; Clarke, K; Francis, J; Myerson, S; Neubauer, S (2011)
To determine the accuracy of visual analysis of left ventricular (LV) function in comparison with the accepted quantitative gold standard method, cardiac magnetic resonance (CMR). Cine CMR imaging was performed at 1.5 T on 44 patients with a range of ejection fractions (EF, 5-80%). Clinicians (n = 18) were asked to visually assess EF after sequentially being shown cine images of a four chamber (horizontal long axis; HLA), two chamber (vertical long axis; VLA) and a short axis stack (SAS) and results were compared to a commercially available analysis package. There were strong correlations between visual and quantitative assessment. However, the EF was underestimated in all categories (by 8.4% for HLA, 8.4% for HLA + VLA and 7.9% for HLA + VLA + SAS, P all < 0.01) and particularly underestimated in mild LV impairment (17.4%, P < 0.01), less so for moderate (4.9%) and not for severe impairment (1%). Assessing more than one view of the heart improved visual assessment of LV, EF, however, clinicians underestimated EF by 8.4% on average, with particular inaccuracy in those with mild dysfunction. Given the important clinical information provided by LV assessment, quantitative analysis is recommended for accurate assessment.